MicroRNA levels are modulated in Aedes aegypti after exposure to Dengue‐2. Issue 1 (15th November 2013) - Campbell, C. L.; Harrison, T.; Hess, A. M.; Ebel, G. D.
Abstract To define microRNA (miRNA) involvement during arbovirus infection of Aedes aegypti, we mined deep sequencing libraries of Dengue type 2 (DENV2)‐exposed mosquitoes. Three biological replicates for each timepoint [2, 4 and 9 days post‐exposure (dpe)] and treatment group allowed us to remove the outliers associated with sample‐to‐sample variability. Using edgeR (R Bioconductor), designed for use with replicate deep sequencing data, we determined the log fold‐change (logFC) of miRNA levels [18–23 nucleotides (nt)]. The number of significantly modulated miRNAs increased from ≤5 at 2 and 4 dpe to 23 unique miRNAs by 9 dpe. Putative miRNA targets were predicted by aligning miRNAs to the transcriptome, and the list was reduced to include the intersection of hits found using the Miranda, PITA, and TargetScan algorithms. To further reduce false‐positives, putative targets were validated by cross‐checking them with mRNAs reported in recent DENV2 host response transcriptome reports; 4076 targets were identified. Of these, 464 gene targets have predicted miRNA‐binding sites in 3′ untranslated regions. Context‐specific target functional groups include proteins involved in transport, transcriptional regulation, mitochondrial function, chromatin modification and signal transduction processes known to be required for viral replication and dissemination. The miRNA response is placed in context with other vector host response studies by comparing the predicted targets with those of transcriptome studies. Together, these data are consistent with the hypothesis that profound and persistent changes to gene expression occur in DENV2‐exposed mosquitoes.